Steeling the Mind Combat Stress Reactions and Their Implications for Urban Warfare - Helmus, Todd C. (RAND Corporation, 2005)
Combat stress casualties are not necessarily higher in city operations than operations on other types of terrain. Commanders and NCOs need to have the skills to treat and prevent stress casualties and understand their implications for urban operations. The authors review the known precipitants of combat stress reaction, its battlefield treatment, and the preventive steps commanders can take to limit its extent and severity.